Rare case of synovial sarcoma of anterior abdominal wall in a young Indian male - Katyal, Abhishek; Patel, Yash (International Surgery Journal, 2017)
Synovial Sarcomas (synoviomas) are the fourth most common malignant soft-tissue tumours, and typically develop in para-articular locations of the extremities in close association with joint capsules, tendon sheaths, bursae and fascial structures. Other less common sites include the head and neck, abdominal wall, intra-abdominal cavity, and mediastinum. In this article, an interesting and rare case of a 25-year-old man with left upper abdominal lump is reported which was subsequently diagnosed as biphasic synovial sarcoma (spindle cell variety) of anterior abdominal wall.